Effect of Workload and Organizational Communication on Employee Performance of PT. Abasando Prima Indonesia - Syahrul Muhammad Aljupri,; Shinta Oktafien, (Technium Social Sciences Journal, 2021)
Today, the development of technology and science is very rapid in order to create convenience for the community and every company in the world, especially Indonesia. The development of technology in the industrial world began in the 18th century, when agricultural societies became more advanced and urban. In this study the authors took the object of research at PT. Abasando Prima Indonesia with the title Effect of Workload and Communication on Employee Performance. This research uses quantitative methods with descriptive analysis approach and verification. The results of descriptive analysis of the workload stated that it was quite good, organizational communication said it was good enough and the performance was quite high. The verification analysis states that the partial hypothesis of workload has a significant effect on employee performance and organizational communication has a significant effect on employee performance, while simultaneously states that workload and organizational communication have a significant effect on employee performance. Suggestions for companies, namely PT. Abasando Prima Indonesia anticipates the mental burden of employees, PT. Abasando Prima Indonesia anticipates the mental burden of employees and PT. Abasando Prima Indonesia must be able to improve the quality of employees properly, because if the quality of employees is still low it will reduce the employee's performance.